Distribution Network Differential Protection Technology Based on 5G Communication and Improved DTW - YU Yang; TANG Wei; YE Yuanbo; SHAO Qingzhu; YANG Ruijin; HUANG Yuhui (Journal of Harbin University of Science and Technology)
With a large number of distributed power generations connected to the distribution network, the distribution network has gradually transformed into a multi-source and multi-terminal network, and the requirements for relay protection performance are increasing. Current differential protection is suitable for the problem of multi-source network failure in distribution networks, but differential protection relies on fibre channel, which has problems such as high cost and difficult laying, which is difficult to promote and use. This paper proposes a distribution network differential protection scheme based on 5G communication, which aims to replace optical fiber by using the advantages of low latency and low cost of 5G communication and improve the practicality of differential protection of distribution network. To solve the problem of communication delay and delay jitter, an improved dynamic time programming (DTW) algorithm was introduced. Aiming at the shortcomings of traditional DTW algorithms, such as large overhead, algorithm accuracy and efficiency limited by sequence amplitude difference, and empirical selection of parameters, the global path constraint strategy, data standardization strategy and particle swarm optimization strategy are proposed to be improved. Simulation results show that the differential protection method of distribution network based on 5G communication and improved DTW is selective and fast,and can be reliably operated in different scenarios.